Machine Learning - Mitchell, Tom M. (McGraw-Hill, 1997)
This book covers the field of machine learning, which is the study of algorithms that allow computer programs to automatically improve through experience. The book is intended to support upper level undergraduate and introductory level graduate courses in machine learning.